Impact of Seminal Chemical Elements on the Oxidative Balance in Bovine Seminal Plasma and Spermatozoa. (9th September 2013) - Tvrdá, Eva; Lukáč, Norbert; Schneidgenová, Monika; Lukáčová, Jana; Szabó, Csaba; Goc, Zofia; Greń, Agnieszka; Massányi, Peter
Abstract : Mutual relationships between selected chemical elements (Na, K, Fe, Cu, Mg, and Zn), basic motility characteristics (motility and progressive motility), and markers of the oxidative balance (superoxide dismutase, catalase, glutathione, albumin, and malondialdehyde) were investigated in bovine seminal plasma and spermatozoa. Computer assisted sperm analysis was used to assess the motility parameters; mineral concentrations were determined by the voltammetric method and flame absorption spectrophotometry; antioxidants and malondialdehyde were evaluated by UV/VIS spectrophotometry. Concentrations of chemical elements in both seminal fractions were in the following descending order: Na > K > Zn > Mg > Fe > Cu. Higher amounts of all minerals and nonenzymatic antioxidants were detected in the seminal plasma (P < 0.01 ;P < 0.001 ), while higher MDA concentration and activity of enzymatic antioxidants were recorded in the cell lysates (P < 0.01 ;P < 0.001 ). Na, Fe, Cu, Mg, and Zn were positively correlated with the motility and antioxidant parameters (P < 0.05 ;P < 0.01 ;P < 0.001 ). Inversely, K exhibited the positive associations with malondialdehyde (P < 0.05 ). This study demonstrates that most chemical elements are integral components of bovine semen and are needed for the protection against oxidative stress development.